The Influence of Demographic Factors on Men’s Purchase Intentions Towards Sustainable Products - Goel, Divya; Gujral, Meenakshi; Jaiswal, Pooja; Yadav, Anuja (Journal of Neonatal Surgery, 2025)
This research examines how demographic variables affect men's attitudes and buying intentions towards green personal care products in contemporary retail stores. In response to increasing environmental consciousness and ethical consumption, it is imperative for marketers and policymakers to know the impact of demographics on consumer behavior. The study employs a quantitative method, where there were structured questionnaires administered to 650 male participants from varying age groups, income levels, education, and marital status. Statistical tests such as regression and correlation were conducted to identify that education and income are strong predictors of positive attitudes and purchasing intent toward green personal care products. The strongest predictor was found to be education, suggesting that higher-educated individuals tend to embrace sustainable consumption. Moreover, marital status and age have positive correlations as well, implying that family and personal responsibilities might raise sensitivity toward green products. The research helps the literature of consumer behavior by indicating how demographic segments react differently to sustainability efforts in personal care. Practical implications imply that greening strategies should be customized based on demographic profiles so that market penetration is improved. The work promotes further research on psychological and cultural factors for a deeper insight into green consumerism